2018
DOI: 10.1002/hbm.24336
|View full text |Cite
|
Sign up to set email alerts
|

Sustained versus instantaneous connectivity differentiates cognitive functions of processing speed and episodic memory

Abstract: Synchrony of brain activity over time describes the functional connectivity between brain regions but does not address the temporal component of this relationship. We propose a complementary method of analysis by introducing the width of cross-correlation curves between functional MRI (fMRI) time series as a metric of the relative duration of synchronous activity between brain regions, or "sustained connectivity". Using resting-state fMRI, cognitive, and demographics data from 1,003 subjects included in the Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 94 publications
(134 reference statements)
1
24
0
Order By: Relevance
“…King et al found increased durations of functional connections in both individual brain regions and distributed networks in autism, which were associated with metrics of disease severity [King et al, ]. They used a complementary method of analysis by introducing the width of cross‐correlation curves between resting‐state fMRI time series as a metric of relative duration of synchronous activity between brain regions (“sustained connectivity”) [King & Anderson, ]. The persistence of brain connectivity in autism may limit the ability to rapidly shift from one brain state to another [King et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…King et al found increased durations of functional connections in both individual brain regions and distributed networks in autism, which were associated with metrics of disease severity [King et al, ]. They used a complementary method of analysis by introducing the width of cross‐correlation curves between resting‐state fMRI time series as a metric of relative duration of synchronous activity between brain regions (“sustained connectivity”) [King & Anderson, ]. The persistence of brain connectivity in autism may limit the ability to rapidly shift from one brain state to another [King et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…16 Briefly, time series data from each of the 17 distributed brain networks were extracted for analysis with each network treated as a single region of interest (ROI).…”
Section: Methodsmentioning
confidence: 99%
“…35 When combined, this parcellation scheme incorporates major cortical, subcortical, and cerebellar gray matter ROIs numbering 361 regions in total. 16,36 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations